Analisis Penyebab Kesulitan Keuangan (Financial Distress) pada Bidang Konstruksi di PT Adhitama Global Mandiri - Fransisca Aprilia Khancitra Subekti; Irawan Budi Prasetyo (Bulletin of Management and Business, 2022)
The purpose of this study is to analyze the internal factors that led to PT. Adhitama Global Mandiri experiencing financial distress (financial distress) and to provide advice and input to the company in order for it to resolve and handle the financial distress condition. The research object under consideration is one of PT. Adhitama Global Mandiri's projects, namely the construction of the Achievement Arena Building, Faculty of Administrative Sciences, Universitas Brawijaya. Financial distress (financial distress) at PT. Adhitama Global Mandiri was caused by (1) cash difficulties, (2) large amounts owed to subcontractors, suppliers, and banks, and (3) company receivables. The analytical technique causing financial distress at PT. Adhitama Global Mandiri is to: (1) generate cash financial statements from the contract value, (2) generate financial reports payable to subcontractors, suppliers, and banks, and (3) generate financial statements of Brawijaya University receivables to PT. Adhitama Global Mandiri.